Revisiting Late Pleistocene Loess–Paleosol Sequences in the Azov Sea Region of Russia: Chronostratigraphy and Paleoenvironmental Record - Chen, Jie; Stevens, Thomas; Yang, Taibao; Qiang, Mingrui; Matishov, Gennady; Konstantinov, Evgeny; Kurbanov, Redzhep; Zeng, Biao; Shi, Peihong (Frontiers in Earth Science, 2022)
Loess-paleosol sequences are the most intensively studied terrestrial archives used for the reconstruction of Late Pleistocene environmental and climatic changes in the Azov Sea region, southwest Russia. Here we present a refined chronostratigraphy and a multiproxy record of Late Pleistocene environmental dynamics of the most complete and representative loess–paleosol sequences (Beglitsa and Chumbur-Kosa sections) from the Azov Sea region. We propose a new chronostratigraphy following the Chinese and Danubean loess stratigraphic models that refines the subdivision of the Last Interglacial paleosol (S1) complex in two Azov Sea sites, resolve the uncertainty of the stratigraphic position of the weakly developed paleosol (L1SSm) in Beglitsa section, and allow for direct correlation of the Azov Sea sections with those in the Danube Basin and the Chinese Loess Plateau. More importantly, it may serve as a basis for better constraining local and regional chronostratigraphic correlations, and facilitate the interpretation of climatic connections and possible forcing mechanisms responsible for the climatic trends in the region. In addition, a general succession of environmental dynamics is reconstructed from these two vital sections, which is broadly consistent with other loess records in the Dnieper Lowland and Lower Danube Basin, demonstrating similar climatic trends at Glacial–Interglacial time scales. Furthermore, our results have important implications for the chronostratigraphic representativeness of Beglitsa as a key regional loess section and for the reconstruction of the temporal and spatial evolution of Late Pleistocene climate in the Azov Sea region.